Protein intake from different sources and cognitive decline over 9 years in community-dwelling older adults - Gao, Rongtao; Yang, Zhan; Yan, Wenju; Du, Weiping; Zhou, Yuan; Zhu, Feng (Frontiers in Public Health, 2022)
Objectives To examine the association of protein intake from different sources with cognitive decline. Methods Our analysis included 3083 participants aged 55-93 years from the China Health and Nutrition Survey. Cognition was assessed in 1997, 2000, 2004, 2006, and 2015. Diet was assessed using weighing methods in each survey. Results During a follow-up of 9 years, participants in quintile 5 of plant protein intake (% energy) had a higher risk (odds ratio (95% CI): 3.03 (1.22-7.53)) of cognitive decline compared with those in quintile 1. Higher animal protein intake (% total protein) was associated with a lower risk of cognitive decline (odds ratio (95% CI) for quintile 5 versus quintile 1: 0.22 (0.07-0.71)). Grains protein intake was inversely but fish/shrimp and poultry protein intake were positively associated with change in cognitive Z-score. Conclusion Increasing animal protein consumption in a population with plant dominant diets may help to prevent cognitive decline.